Understanding and Modeling Förster-type Resonance Energy Transfer (FRET) Introduction to FRET, Vol. 1 - Govorov, Alexander; Hernández Martínez, Pedro Ludwig; Demir, Hilmi Volkan (Nanoscience and Nanotechnology, 2016)
This Brief presents a historical overview of the Förster-type nonradiative energy transfer and a compilation of important progress in FRET research, starting from Förster until today, along with a summary of the current state-of-the-art. Here the objective is to provide the reader with a complete account of important milestones in FRET studies and FRET applications as well as a picture of the current status.